9y-1=-10+12y

Simple and best practice solution for 9y-1=-10+12y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y-1=-10+12y equation:


Simplifying
9y + -1 = -10 + 12y

Reorder the terms:
-1 + 9y = -10 + 12y

Solving
-1 + 9y = -10 + 12y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-12y' to each side of the equation.
-1 + 9y + -12y = -10 + 12y + -12y

Combine like terms: 9y + -12y = -3y
-1 + -3y = -10 + 12y + -12y

Combine like terms: 12y + -12y = 0
-1 + -3y = -10 + 0
-1 + -3y = -10

Add '1' to each side of the equation.
-1 + 1 + -3y = -10 + 1

Combine like terms: -1 + 1 = 0
0 + -3y = -10 + 1
-3y = -10 + 1

Combine like terms: -10 + 1 = -9
-3y = -9

Divide each side by '-3'.
y = 3

Simplifying
y = 3

See similar equations:

| -5(7n-4)+3= | | 2y-14=4y+4 | | P=2(26)+2(91) | | 5y+6y-81=7y+102+65 | | 3t^4=8t | | x+x+125000=550000000 | | 12x+8y-12=0 | | 4*x-9/2+12=0 | | 51x^2-5x-4= | | x+x+4=238 | | -(6y+5)-(-5y-7)=-5 | | 14-2x+39x-18x=256-60x-657x | | 13-42/7 | | 7+3p-4=9p+10-5p | | -x/3+58= | | -3b=-12 | | 2b+3(b-2)=4 | | -14n+4=-13n-17 | | -8w^2-8w+19=0 | | 12y=11(y+1) | | 4n+10n=28 | | -7.7x=15.4 | | 7-(5x-12)=1/3(4x+60) | | 16-11x+12=-15x | | -57+23+x= | | r-15=-13 | | t(4+1)=0 | | 1.6q-3.3-2.2q=-1.6q-4.7 | | 2x+0.8-3.5=x | | 37x-625=0 | | 36= | | 25s^2+90sp+81p^2= |

Equations solver categories